Cellular and molecular characterisation of the peripheral immune environment in migraine - Jayden A. O'Brien; Benjamin Heng; Seong Beom Ahn; Ananda Staats-Pires; Ashleigh Wake; Rebecca Wong; Aimie L. Peek; Noemi Meylakh; Karl Ng; Richard Stark; Vaughan G. Macefield; Helen M. McGuire; et al. (PAIN Reports)
Abstract. Introduction:. Peripheral immune dysfunction may be critically involved in the pathophysiology of migraine. Some evidence supports a role for peripheral T cells, monocytes, and humoral factors including kynurenine metabolites and cytokines, however a comprehensive picture has yet to emerge. Objective:. This study sought to undertake a systematic assessment of the immune changes in episodic and chronic migraine across phases of the migraine cycle. Methods:. Migraine patients in different phases of the migraine cycle with a confirmed diagnosis of episodic or chronic migraine and age- and sex-matched healthy controls were recruited. Peripheral blood was assessed for circulating immune cells, plasma proteins, and kynurenine pathway metabolites in a cross-sectional case–control design. Data were acquired using high-dimensional approaches including proteomics, single-cell mass cytometry, and imaging flow cytometry. Results:. Plasma proteins related to increased cell–cell adhesion and altered enzymatic activity were increased in migraine. The migraine prodrome displayed a strong and distinct proinflammatory phenotype defined by increased platelet-neutrophil aggregation, quinolinic acid production, and matrix metalloproteinase-9 expression. Migraine patients in the attack phase instead expressed higher levels of cytokine receptors and phosphorylated transcription factors in Th17 cells, monocytes, natural killer cells, and B cells. T cells were shifted to a mobilised, recirculating phenotype across all migraine phases. Episodic and chronic migraine patients were only distinguished by subtle changes in T-cell phenotype. Conclusion:. Distinct proinflammatory peripheral signatures were detected between migraine phases, while few alterations distinguished episodic and chronic status. These data provide a resource that may aid in the identification of peripheral immune cells and mediators contributing to migraine attack onset.